2021
DOI: 10.1002/cssc.202101037
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of 5‐Hydroxymethylfurfural (HMF)‐Metal Interactions on the Electrochemical Reduction Pathways of HMF on Various Metal Electrodes

Abstract: 5‐Hydroxymethylfurfural (HMF), which can be derived from lignocellulosic biomass, is an important platform molecule that can be used to produce valuable biofuels and polymeric materials. Electrochemical reduction of HMF is of great interest as it uses water as the hydrogen source and achieves desired reduction reactions at room temperature and ambient pressure. Hydrogenation and hydrogenolysis are two important reactions for reductive HMF conversion. Therefore, elucidating key characteristics of electrocatalys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
55
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 34 publications
(60 citation statements)
references
References 37 publications
4
55
1
Order By: Relevance
“…The higher activity of Ni in the HER shifts the onset in the borate electrolyte towards less cathodic potentials (Figure 1). Remarkably, the addition of HMF to the borate buffer does not significantly modify the LSV curve as recently reported for a Ni plate [35] . Despite the absence of the characteristic HMF reduction peak in the voltammogram, the catalyst is active in the reduction of HMF.…”
Section: Resultssupporting
confidence: 76%
See 2 more Smart Citations
“…The higher activity of Ni in the HER shifts the onset in the borate electrolyte towards less cathodic potentials (Figure 1). Remarkably, the addition of HMF to the borate buffer does not significantly modify the LSV curve as recently reported for a Ni plate [35] . Despite the absence of the characteristic HMF reduction peak in the voltammogram, the catalyst is active in the reduction of HMF.…”
Section: Resultssupporting
confidence: 76%
“…Remarkably, the addition of HMF to the borate buffer does not significantly modify the LSV curve as recently reported for a Ni plate. [35] Despite the absence of the characteristic HMF reduction peak in the voltammogram, the catalyst is active in the reduction of HMF. At À 0.51 V vs. RHE it reaches a 36 % conversion, though the selectivity and FE are largely decreased, 40 and 14 %, respectively (Figure 8).…”
Section: Chemsuschemmentioning
confidence: 99%
See 1 more Smart Citation
“…[98] More recently, Lee et al demonstrated HMF-metal interactions on the electrochemical reduction over various metal electrodes (Ti, W, Fe, Co, Ni, Cu, Ag, Cd, and In). [95] The adsorption energy of HMF on the metal surface and the intramolecular bond lengths in HMF were affected by electrode type. More importantly, the selectivity for the hydrogenation and hydrogenolysis of HMF was also determined by HMF-Metal interactions.…”
Section: Electrocatalytic Hydrogenation Pathwaymentioning
confidence: 99%
“…This study elucidated the universal and key factors that affect the selectivity of the HMF hydrogenation, which is favorable for designing more selective electrocatalysts. [95] Utilizing water as a hydrogen source instead of high-cost H 2 gas via ECH for the selective hydrogenation of HMF is a green and sustainable approach that can be carried out under low operating temperatures and pressures. Moreover, the simultaneous oxidation and hydrogenation of HMF can be achieved over paired cells.…”
Section: Electrocatalytic Hydrogenation Pathwaymentioning
confidence: 99%